Innovation pédagogique à l’université : comparaison entre apprentissage par problèmes et cours traditionnel - Perrine Martin; Philippe Padula (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Faced with a massive influx of students without a common educational foundation and background, the issue of knowledge transfer and of the development of teaching practices in higher education is currently at the crux of the debate. We assist in the development of a variety of educational experiments within universities (Clanet, 2001), thus calling into question the relevance of lectures. Yet, a number of professors continue to teach the "traditional" way. The question of the effectiveness of these educational implementations compared to a traditional class consequently still arise. Our study is interested in measuring and comparing the effectiveness of a Problem-based Learning (PBL) compared to a traditional education in a Program Master’s degree Engineering on the unit of education : Study of Mechanical Systems. Our results suggest that the Problem-based learning are effective, and this rapidly for students who are not used to active learning. Starting students going, responsibility awareness, and students’ commitment are certainly factors of success to explore.